The Influence Of Leadership And Performance On The Motivation Of Participants Education And Training - Yusnidar Yusuf (STAI Miftahul Ula Nganjuk, 2017)
Participants education and training at Human Resource Development Centre of Transport Apparatus became the object of research to take the extent of the condition of leadership and performance effect on there work unit participants education and training and by SPSS through linear regression analysis showed that: Partially t-test results showed that the leadership (X1) had a strong and significant influence on employee performance (Y), for t > ttable was 4.829 > 1.96. Similarly, the X2 form of motivation showed tcount > ttable was 6.639> 1.96. The independent variable X1 (Leadership) and X2 (performance) simultaneously tested by F test strong and significant influence on the dependent variable Y (Performance Officer), since Fcount > Ftable (614.059 > 3.07). The resulted of regression equation Y = 2.254 + 0.411 X1 + 0.541 X2. The diversity of variable Y was influenced by the diversity of variables X1 and X2 for the remaining 91.7% 8.3% influenced by other factors. This was due to factors leadership and performance indispensable and always needed to obtain an increase motivation of participants education and training.